Congenital Transmission of Apicomplexan Parasites: A Review - Rojas-Pirela, Maura; Medina, Lisvaneth; Rojas, Maria Verónica; Liempi, Ana Isabel; Castillo, Christian; Pérez-Pérez, Elizabeth; Guerrero-Muñoz, Jesús; Araneda, Sebastian; Kemmerling, Ulrike (Frontiers in Microbiology, 2021)
Apicomplexans are a group of pathogenic protists that cause various diseases in humans and animals that cause economic losses worldwide. These unicellular eukaryotes are characterized by having a complex life cycle and the ability to evade the immune system of their host organism. Infections caused by some of these parasites affect millions of pregnant women worldwide, leading to various adverse maternal and fetal/placental effects. Unfortunately, the exact pathogenesis of congenital apicomplexan diseases is far from being understood, including the mechanisms of how they cross the placental barrier. In this review, we highlight important aspects of the diseases caused by species of Plasmodium, Babesia, Toxoplasma, and Neospora, their infection during pregnancy, emphasizing the possible role played by the placenta in the host-pathogen interaction.